Reinventing Universities: Navigating Technological and Ideological Disruptions In the 21st Century - Tudor Țiclău; Cristina Hințea (Transylvanian Review of Administrative Sciences, 2024)
Universities have historically been pivotal in societal development, serving primarily as (1) ‘knowledge generating institutions’, (2) structural elements of the welfare state promoting the democratization of education, and (3) direct contributors to economic development and social integration. Despite their consolidated and expanded roles, the 21st century presents a series of profound challenges that threaten these traditional functions and the legitimacy of their position. These challenges include (1) increased competition from non-academic actors, (2) shifts in political ideologies, and (3) rapid technological advancements, particularly artificial intelligence. Collectively, these factors pose a potential existential threat to the traditional model of the university. This essay critically examines the current position of universities amidst these disruptive changes and explores the pressures to reinvent themselves to preserve their role as essential contributors to human development.